Model-based path planning for 3D object inspection - Ang, Jun Kai (2019)
Inspection of 3D objects deals with many various ways of approach using several software developments. For this project, it has been developed for doing a path planning on a 3D object through viewpoints using the software available. This final year project aims to apply the knowledge of software using MATLAB programming to solve the solution of directing the path designated across any selected points on a 3D meshed object in MATLAB and described the path planning procedure based on CAD model. The meshed object of inspection used in this project is an 3D aircraft plot, and it consists of several coordinates located on the object itself. In this project, we can make use of navigation, mapping, planning, and tracking of location. There is some background information with relation to the nature of the project. Besides designing and running the program, the results obtained would be also discussed and analysed.